The Intermarium As a Pivotal Geopolitical Buzzword - Kushnir, Ostap (East/West, 2021)
This article focuses on historical and contemporary connotations of the Intermarium concept—Ukrainian and Polish academic and political thought on how to organize and govern the space between the Baltic and Black seas—employing the ideas of Józef Piłsudski, Józef Beck, Michał Czajkowski (Mykhailo Chaikovs'kyi), Mykhailo Drahomanov, members of the Brotherhood of Saints Cyril and Methodius, and other intellectuals. In this context, it traces Ukraine’s and Poland’s attempts to construct Intermarium-type intergovernmental frameworks in the aftermath of the Cold War. It also examines the current stage of Ukrainian-Polish co-operation—the latter being regarded by Intermarium founding fathers as a vital precondition for this framework to be realized. In this respect, the article considers bilateral advancements in political, economic, cultural, and security spheres. As the emergence of a Ukrainian-Polish institutionalized linchpin is impossible in the contemporary geopolitical architecture, the article proposes that the term “Intermarium” has become ambiguous. If by chance the Intermarium comes into being as a defensive alliance today, it might bring more harm than benefit to the regional security.